Arabic calligraphy in Andalusia and Ottoman houses: a comparative analysis - Ziad Baydoun; , Zumahiran Kamarudin (Universitas Negeri Malang, 2021)
Islamic calligraphy during the Andalusian and Ottoman civilizations and after the spread of Islam greatly affected the advancement of decorative art in architecture and the built environment. During that time, Arabic calligraphy has been developed between those two eras. Although Arabic calligraphy was very famous and popular in the past, modern designers can still create a repeated copy of it. The study's objectives are to determine the differences in using Arabic calligraphy between Ġazaleh house, which is from the Ottoman period, and Patio de la Acequia, which is from the Andalusian time and to analyze the usage of Arabic calligraphy in these two houses accordingly. This research involved an analytical review of the Arabic calligraphy found in the mentioned two houses—a comparative analysis between Ġazaleh house and Patio de la Acequia. The study illustrates the application of Arabic scripts in the house's decorations on the Location, placement in the interior or exterior space, and the materials used in the application of the scripts of Arabic calligraphy used in the chosen case studies. The comparison will cover the main components principles used in the Arabic calligraphy scripts in both houses.